PERAN DUKUNGAN SOSIAL DALAM PEMULIHAN BAGI ANAK YANG MENGALAMI DEPRESI BERAT DI YAYASAN RSJ NURROHMAN KASEMEN, SERANG-BANTEN - Dila Shiva Sabilla; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to describe the forms of family social support for people with mental disorders (ODGJ) and the changes that occur during the healing process. The method used by researchers is a qualitative research method with a case study approach. The data collection technique in this research was interviews and documentation with 3 participants and 5 significant other people. The three participants are family members of ODGJ who care for and live with ODGJ, while the 5 significant others are 3 other family members of ODGJ and 2 medical staff who treat ODGJ. The data analysis technique used is thematic data analysis technique. This research shows that the family social support provided is in the form of emotional support, informative support, instrumental support and assessment support as appreciation for ODGJ. The social support provided by the family to ODGJ helps ODGJ experience progress or positive changes. This also shows that family social support has a positive impact that can help the healing process of ODGJ.